Many inpatients may not be physically prepared for community ambulation on discharge from a publicly funded rehabilitation centre: a cross-sectional cohort study. Issue 25 (4th December 2021) - Snowdon, David A.; Sounthakith, Vatthana; Kolic, Jessica; Brooks, Sarah; Scanlon, Sinead; Taylor, Nicholas F.
Abstract: Purpose: We assessed the ability of patients discharging home from inpatient rehabilitation to meet criteria for community ambulation. Methods: Cross-sectional observational study design. Participants were assessed, within 48-hours of discharge on their ability to: ascend/descend three steps, walk at a speed of 0.44 m/s, ascend/descend a slope, ascend/descend a kerb, and walk 315 m continuously. Demographic data were collected from medical records. Multiple logistic regression determined factors predictive of meeting criteria. Results: Of 200 participants (mean 73 years, 66% women, mixed diagnosis), 64 (32%) met all criteria. The least commonly met criteria were walking 315 m continuously (37%) and ascending/descending steps (70%). Participants who were female (OR: 0.27, 95%CI: 0.12–0.61), with a high comorbidity index (OR: 0.71, 95%CI: 0.56–0.91) or a traumatic orthopaedic diagnosis (OR: 0.22, 95%CI: 0.05–0.96) were less likely to meet all criteria. Participants with a higher admission functional independence walk item score (OR: 1.37, 95%CI: 1.05–1.78) or higher ambulatory self-confidence (OR: 1.02, 95%CI: 1.01–1.04) were more likely to meet all criteria. Conclusions: Approximately, one-third of inpatients discharged home from a publicly funded rehabilitation centre met the community ambulation criteria, suggesting many may not be physically prepared to participate in their community. Implications for Rehabilitation: Only about one in three inpatients discharging home from a publicly funded rehabilitation centre met physical criteria for community ambulation. Patients discharging home from inpatient rehabilitation have most difficulty walking long distances (≥315 m) compared to other criteria required for community ambulation (i.e., walking at a speed of 0.44 m/s, stepping up/down a kerb, ascending/descending a slope and ascending/descending three steps) and rehabilitation during this phase may require an increased focus on improving walking endurance/physical activity. Women with a high co-morbidity index, traumatic orthopaedic diagnosis, low self-confidence with ambulation on discharge and who require more assistance with walking on admission are least likely to meet the physical criteria for community ambulation at discharge, and therefore may require additional rehabilitation or supports.